Analysis and modelling of ultracapacitor - Rai, Nor Akmal (2015)
Ultracapacitor is one of most popular device for energy storage system because of it capability that have high charge/discharge efficiency, can operate at high current, have long life cycle and no chemical reaction involve in store and release of energy. Ultracapacitor modelling is important for the electrical system analysis and equipment design. An efficient and high accuracy model can help electrical engineers thoroughly understand ultracapacitor’s characteristics. A commercial ultracapacitor cell is characterized under standard procedures to assess its performance. This project focuses on the analysis and modelling of ultracapacitor cell characteristic. Two experiments involve which are charging/discharging test and AC Impedance test. The charge / discharge test is to determine ultracapacitor cell ability on charge and discharge performance. AC impedance test/ Electrochemical impedance spectroscopy (EIS) is to measure the complex impedance of ultracapacitor. The purpose of the test is to determine capacitance and equivalent series resistance. Based on experiment result, parameters and analysis, the equivalent circuit model of ultracapacitor is proposed. After that, the proposed model is simulated with MATLAB/Simulink and EIS Spectrum Analyser for verification. Then, the simulation result carried out is analysed and compared with experiment results. Based on ultracapacitor characteristic, the electrical circuit modelling was present in this thesis and can be used for power electronic, backup memory, heavy transportation application, hybrid electric vehicles and as power back up for UPS application.